Pengaruh Kepuasan Kerja, Motivasi dan Kompensasi Terhadap Produktivitas Karyawan di Industri Manufaktur (Studi pada Karyawan PT. Daimatu Industri Indonesia ) - Hasanah, Hilda Hidayatul; Slamet, Afi Rachmat; Mustapita, Arini Fitria (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of job satisfaction, motivation, and compensation on employee productivity at PT. Daimatu Industri Indonesia. The research method employed a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 50 respondents using a saturated sampling technique. Data analysis was conducted using multiple linear regression with the assistance of SPSS. The results indicate that job satisfaction, motivation, and compensation simultaneously have a significant effect on employee productivity. Partially, job satisfaction and motivation have a positive and significant effect, while compensation has a significant negative effect on productivity. The coefficient of determination (Adjusted R²) of 22.2% shows that the independent variables explain only a small portion of the variation in employee productivity, with the remaining 77.8% influenced by other factors outside the model. These findings suggest that the company should focus more on improving job satisfaction and employee motivation, while also reevaluating the compensation system to ensure it does not negatively impact productivity. This research contributes to the development of human resource management theory and provides practical insights for manufacturing companies in formulating strategies to enhance employee productivity. Keywords: Job Satisfaction, Motivation, Compensation, Employee Productivity